Strategies in supporting inclusive education for autistic students—A systematic review of qualitative research results. (September 2022) - Petersson-Bloom, Linda; Holmqvist, Mona
Background and Aim: Strategies to modify and adjust the educational setting in mainstream education for autistic students are under-researched. Hence, this review aims to identify qualitative research results of adaptation and modification strategies to support inclusive education for autistic students at school and classroom levels. Method: In this systematic review, four databases were searched. Following the preferred PRISMA approach, 108 studies met the inclusion criteria, and study characteristics were reported. Synthesis of key findings from included studies was conducted to provide a more comprehensive and holistic understanding. Main Contribution: This article provides insights into a complex area via aggregating findings from qualitative research a comprehensive understanding of the phenomena is presented. The results of the qualitative analysis indicate a focus on teachers' attitudes and students' social skills in research. Only 16 studies were at the classroom level, 89 were at the school level, and three studies were not categorized at either classroom or school level. A research gap was identified regarding studies focusing on the perspectives of autistic students, environmental adaptations to meet the students' sensitivity difficulties, and how to enhance the students' inclusion regarding content taught and knowledge development from a didactic perspective. Conclusions and Implications: Professional development that includes autism-specific understanding and strategies for adjusting and modifying to accommodate autistic students is essential. This conclusion may direct school leaders when implementing professional development programs. A special didactical perspective is needed to support teachers' understanding of challenges in instruction that autistic students may encounter.